irpll Teaching English as a Second Language through Aesthetic Pleasure and Moral Lesson to Punjabi and Pashto Speaking Students at Intermediate Level: Shehbaz Afzal Bezar,Naseem Tareen Shabab - jan, abdullah (JPL, 2023)
English being a global language is expanding from Inner Circle to Outer and Expanding Circle. There is a relationship between ESL and literature. English is a compulsory part of syllabi designed for Punjabi and Pashto speaking students. Only a small number of research scholars have examined gender issues and significance of poetry portion in the course of intermediate but utilizing that course in order to enhance English vocabulary of Punjabi and Pashto speaking students through aesthetic pleasure and moral lesson has not yet been investigated. The present qualitative study uses analytical-empirical methodology to analyze teaching English through aesthetic pleasure and moral lesson to Punjabi and Pashto speaking students at intermediate level. There might be focus on changing techniques for teaching literature portion: the teachers‘ involvement; not mechanical teaching and mechanical reading of the texts on the part of the students; the teachers‘ pinpointing elements of aesthetic pleasure and moral lesson; and the teachers‘ producing eagerness in the students for learning English. The objective of the study is an attempt to utilize the literature portion of the textbooks of English of intermediate of Punjab, KPK and Baluchistan boards for teaching English as a Second Language to Punjabi and Pashto speaking students.